2020
DOI: 10.1111/appy.12440
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Chinese and US practitioners' attitudes towards teletherapy during the COVID‐19 pandemic

Abstract: Introduction The China American Psychoanalytic Alliance (CAPA) has been offering psychoanalytic psychotherapy training and treatment to Chinese mental health professionals entirely over the Internet since 2006. When the COVID‐19 pandemic began, most practitioners worldwide had to turn to teletherapy. US psychoanalytic practitioners were more negative towards teletherapy than those from other theoretical orientations. We predicted that CAPA practitioners as compared to US psychoanalytic practitioners would be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…To date, studies on the acceptability of COVID-19 vaccination have found moderate to high acceptance rates among adolescents and adults, respectively [ 34 , 35 ]. Predictors of vaccine acceptance include perceived benefits and efficacy of the COVID-19 vaccine [ 36 38 ]. However, findings on vaccine acceptance in the general public are not necessarily applicable to patients with severe psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies on the acceptability of COVID-19 vaccination have found moderate to high acceptance rates among adolescents and adults, respectively [ 34 , 35 ]. Predictors of vaccine acceptance include perceived benefits and efficacy of the COVID-19 vaccine [ 36 38 ]. However, findings on vaccine acceptance in the general public are not necessarily applicable to patients with severe psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Wang, Gordon & Snyder [20] compared psychoanalytically trained Chinese practitioners who received their treatment and training online, with a group of U.S. psychoanalytic practitioners matched for age. They found that the Chinese practitioners had more positive opinions about teletherapy during the pandemic and had more positive opinions about the effectiveness of teletherapy in working with transference, relational issues and resistance.…”
Section: Comfort With the Technologymentioning
confidence: 99%
“…Staff (n=105) Child and adolescent services V, P Description of the implementation of a home-based telemental health service during the pandemic Sharma et al [28] Staff (n=648) Intellectual disabilities NA Survey of the experiences of staff working with people with intellectual and other developmental disabilities Sheehan et al [105] Staff NA NA Exploring the impact of the pandemic on mental health services in Indiana Sklar et al [106] Service users (n=1021) Eating disorders NA Survey to evaluate the impact of the pandemic on people with eating disorders Termorshuizen et al [107] Staff (n=20) Mixed V, P Interviews with psychiatrists to understand how change in delivery has affected mental health care Uscher-Pines et al [108] Staff (n=18) Opiate use disorder V, P Interviews with clinicians to understand the experience of using telemedicine for opiate use disorder Uscher-Pines et al [109] Staff Mixed V Description of transforming a daytreatment program for older people into an online program van Dijk et al [110] Staff (n=329) Mixed V, P Survey to compare Chinese and US practitioners' attitudes toward teletherapy during the pandemic Wang et al [111] Staff (n=363) Perinatal services V, P, M Survey to explore staff perceptions of the impact of the pandemic on perinatal services Wilson et al [112] Service users (n=7) Psychosis and bipolar V Description of the implementation of group teletherapy for people with firstepisode psychosis Wood et al [113] Staff and service users (n=60 therapist/service user dyads) Attention deficit hyperactivity disorder V, P Exploration of the experience of therapy sessions for people with attention deficit hyperactivity disorder and their therapists during the pandemic Wyler et al [114] NA (description of service change) Mixed V, P Description of the rapid conversion of an outpatient psychiatric clinic to a telepsychiatry clinic Yellowlees et al [115] Service users (n=314) Mixed P Audit to understand the move to telephone support for people using a community mental health team Zulfic et al [116] a V: video.…”
Section: Mental Health Problem/diagnosis Modality Used Aim Of Study Studymentioning
confidence: 99%
“…Overall, all settings had sufficient capacity to shift to some delivery of telemental health in a short period. networks and culture of an organization, as well as the implementation climate (eg, capacity for change) [43,52,111] Staff characteristics: Information on the following psycholog-…”
mentioning
confidence: 99%